Niche Laminin and IGF-1 Additively Coordinate the Maintenance of Oct-4 Through CD49f/IGF-1R-Hif-2α Feedforward Loop in Mouse Germline Stem Cells - Au, Heng-Kien; Peng, Syue-Wei; Guo, Chin-Lin; Lin, Chien-Chia; Wang, Yi-Lin; Kuo, Yung-Che; Law, Tsz-Yau; Ho, Hong-Nerng; Ling, Thai-Yen; Huang, Yen-Hua (Frontiers in Cell and Developmental Biology, 2021)
The mechanism how extracellular matrix (ECM) cooperates with niche growth factors and oxygen tension to regulate the self-renewal of embryonic germline stem cells (GSCs) still remains unclear. Lacking of an appropriate in vitro cell model dramatically hinders the progress. Herein, using a serum-free culture system, we demonstrated that ECM laminin cooperated with hypoxia and insulin-like growth factor 1 receptor (IGF-1R) to additively maintain AP activity and Oct-4 expression of AP+GSCs. We found the laminin receptor CD49f expression in d2 testicular GSCs that were surrounded by laminin. Laminin and hypoxia significantly increased the GSC stemness-related genes, including Hif-2α, Oct-4, IGF-1R, and CD49f. Co-treatment of IGF-1 and laminin additively increased the expression of IGF-IR, CD49f, Hif-2α, and Oct-4. Conversely, silencing IGF-1R and/or CD49f decreased the expression of Hif-2α and Oct-4. The underlying mechanism involved CD49f/IGF1R-(PI3K/AKT)-Hif-2α signaling loop, which in turn maintains Oct-4 expression, symmetric self-renewal, and cell migration. These findings reveal the additive niche laminin/IGF-IR network during early GSC development.